Local hippocampal methamphetamine-induced reinforcement - Ricoy, Ulises M.; Martinez Jr., Joe L. (Frontiers in Behavioral Neuroscience, 2009)
Drug abuse and addiction are major problems in the United States. In particular methamphetamine (METH) use has increased dramatically. A greater understanding of how METH acts on the brain to induce addiction may lead to better therapeutic targets for this problem. The hippocampus is recognized as an important structure in learning and memory, but is not typically associated with drug reinforcement or reward processes. Here, the focus is on the hippocampus which has been largely ignored in the addiction literature as compared to the nucleus accumbens (NAc), ventral tegmental area (VTA), and prefrontal cortex (PFC). The results show that METH administered unilaterally via a microdialysis probe to rats’ right dorsal hippocampus will induce drug-seeking (place preference) and drug-taking (lever-pressing) behavior. Furthermore, both of these responses are dependent on local dopamine (DA) receptor activation, as they are impaired by a selective D1/D5 receptor antagonist. The results suggest that the hippocampus is part of the brain’s reward circuitry that underlies addiction.